Disease and democracy : the industrialized world faces AIDS - Baldwin, Peter, 1956- (California/Milbank books on health and the public, 2005)
Disease and Democracy is the first comparative analysis of how Western democratic nations have coped with AIDS. Peter Baldwin's exploration of divergent approaches to the epidemic in the United States and several European nations is a springboard for a wide-ranging and sophisticated historical analysis of public health practices and policies. In addition to his comprehensive presentation of information on approaches to AIDS, Baldwin's authoritative book provides a new perspective on our most enduring political dilemma: how to reconcile individual liberty with the safety of the community. Baldw.